Antitumor Effects of Trimethylellagic Acid Isolated From Sanguisorba officinalis L. on Colorectal Cancer via Angiogenesis Inhibition and Apoptosis Induction - Chongfei Bai; Chongfei Bai; Yueshan Sun; Xianchao Pan; Jing Yang; Jing Yang; Xiaoxuan Li; Anguo Wu; Anguo Wu; Dalian Qin; Dalian Qin; Shousong Cao; et al. (Frontiers Media S.A., 2020)
Previous studies have demonstrated that tannin could inhibit the proliferation and angiogenesis of cancer cells. However, the mechanism(s) associated with its antitumor effect remains unclear. Here, we investigated the effects of 3,3',4'-trimethylellagic acid (TMEA), a tannin compound isolated from Sanguisorba officinalis L., on the proliferation, angiogenesis, and apoptosis in cancer cells, as well as the underlying mechanism(s) related to its antitumor activity. TMEA was isolated from Sanguisorba officinalis L. by silica gel column chromatography. Molecular docking was carried out to assess active pocket binding between TMEA and vascular endothelial growth factor receptor 2 (VEGFR2). The antiangiogenic effect of TMEA on the migration and tube formation was detected in HUVECs by wound healing and tube formation assays, respectively. The antitumor effects of TMEA on the cell proliferation were determined in HepG2, A549, and SW620 cells by MTS assay in vitro and on the tumor growth of SW620 xenografts bearing in nude mice in vivo. The mRNA expression of Bcl-2, Bax, caspase-3, VEGF, PI3K, and mTOR were measured by qRT-PCR and protein expression of Bcl-2, Bax, caspase-3, VEGF, PI3K, and mTOR by Western blotting, and the protein expression of Bcl-2, Bax, caspase-3 and CD31 were detected by immunohistochemical analysis in vivo, respectively. The results showed that TMEA combined with VEGFR2 in the functional pockets of Asn223A, Gly922A, and Leu840A and inhibited the proliferation, migration, tube formation, and expression of VEGF and its downstream signaling mediators in HUVECs. TMEA also significantly inhibited the proliferation of HepG2, A549, and SW620 cancer cells in vitro, and suppressed the growth of SW620 tumors in vivo. Moreover, TMEA upregulated the expression of proapoptotic factors Bax and caspase-3 and downregulated the expression of antiapoptotic factors CD31 and Bcl-2 in cancer cells and/or tumor tissues. The data indicate that TMEA executes its anticancer activity by inducing apoptosis and inhibiting angiogenesis in cancer cells in vitro and tumor growth in vivo. The underlying anticancer mechanism is associated with the apoptotic and VEGF/PI3K/AKT/mTOR pathways.